The Dawn Mission to Minor Planets 4 Vesta and 1 Ceres 2010
DOI: 10.1007/978-1-4614-4903-4_9
|View full text |Cite
|
Sign up to set email alerts
|

HED Meteorites and Their Relationship to the Geology of Vesta and the Dawn Mission

Abstract: Howardite-e ucrite-diogenite (HED) meteorites, thought to be derived from 4 Vesta, provide the best sampling available for any differentiated asteroid. However, deviations in oxygen isotopic composition from a common mass-fractionation line suggest that a few eucrite-like meteorites are from other bodies, or that Vesta was not completely homogenized during differentiation. The petrology and geochemistry of HEDs provide insights into igneous processes that produced a crust composed of basalts, gabbros, and ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 120 publications
(2 reference statements)
10
71
0
Order By: Relevance
“…Alternatively, if the volcanism on Vesta manifested itself only as a global magma ocean, which cooled and crystallized to form basaltic minerals in widespread flow fields as opposed to discrete individual flows (similar to the larger basinfilling lunar maria), then this might also explain the lack of observed volcanic flow features. In either case, the lack of discrete volcanic features on Vesta is consistent with the hypothesis, based on analysis of basaltic material in the HED suite, that volcanism on Vesta occurred only during the first $ 10-100 Ma of Vesta's history (e.g., Schiller et al, 2010;McSween et al, 2011), and that since then impact processes have degraded any ancient volcanic features to the point where they cannot be distinguished. It is possible that ongoing detailed study of Vesta's surface as part of the quadrangle mapping process may yet identify some small battered fragments of ancient volcanic features; perhaps the best place to investigate is Vestalia Terra, which appears to be a continent-sized fragment of Vesta's original crust (Buczkowski et al, 2013), albeit disrupted and blanketed by superposed impact ejecta.…”
Section: Volcanic Hypothesissupporting
confidence: 83%
See 4 more Smart Citations
“…Alternatively, if the volcanism on Vesta manifested itself only as a global magma ocean, which cooled and crystallized to form basaltic minerals in widespread flow fields as opposed to discrete individual flows (similar to the larger basinfilling lunar maria), then this might also explain the lack of observed volcanic flow features. In either case, the lack of discrete volcanic features on Vesta is consistent with the hypothesis, based on analysis of basaltic material in the HED suite, that volcanism on Vesta occurred only during the first $ 10-100 Ma of Vesta's history (e.g., Schiller et al, 2010;McSween et al, 2011), and that since then impact processes have degraded any ancient volcanic features to the point where they cannot be distinguished. It is possible that ongoing detailed study of Vesta's surface as part of the quadrangle mapping process may yet identify some small battered fragments of ancient volcanic features; perhaps the best place to investigate is Vestalia Terra, which appears to be a continent-sized fragment of Vesta's original crust (Buczkowski et al, 2013), albeit disrupted and blanketed by superposed impact ejecta.…”
Section: Volcanic Hypothesissupporting
confidence: 83%
“…Earth-based telescopic observations showed spectral evidence of basaltic mineralogies, and the inferred relationship of the HED meteorites to Vesta is well established (e.g., McCord et al, 1970;Feierberg et al, 1980;Gaffey, 1997;Binzel et al, 1997;Cochran and Villas, 1998) and has been confirmed by the Dawn observations De Sanctis et al, 2012). Petrologic study of the Vesta-derived HED meteorites demonstrates the presence of basaltic minerals and glassy textures that are diagnostic of basaltic lava flows on Earth (McSween et al, 2011(McSween et al, , 2013, or alternatively that these basaltic minerals were derived from crystallization of a global magma ocean that may have once covered Vesta (e.g., Righter and Drake, 1997;Ruzicka et al, 1997;Warren, 1997). Given the strong likelihood of basaltic volcanism on Vesta inferred from telescopic data and the HED connection, Keil (1996, 1997) used mathematic and petrologic models to predict the types of volcanic deposits that should occur on Vesta, including: (a) surface basaltic lava flows with widths of a few hundred meters to a few kilometers, lengths between a few kilometers to several tens of kilometers, thicknesses between 5 and 20 m, and erupted volumes o3 km 3 ; (b) formation of channelized flows on steeper slopes; (c) a lack of uniform sheet flows; d) a lack of shield volcanoes; (e) shallow intrusions (dikes) with widths of $ 1 m and vertical extents of o10 km, (f) deep intrusions (dikes) with thicknesses ≤3 m and lateral extents ≤30 km, and volumes between 3 and 10,000 km 3 ; and (g) explosive eruptions only occurring in the form of optically-dense lava fountains that form lava ponds feeding lava flows, such that no broad pyroclastic fall deposits should occur on Vesta.…”
Section: Volcanic Hypothesismentioning
confidence: 77%
See 3 more Smart Citations